THE CONSUMER ACCEPTANCE ON THE SEAWEED (Eucheuma cottonii) DRINKING JUICE MIXED WITH PANDANUS LEAVES (Pandanus amarylifollius) EXTRACT - Armelia Rahmasari; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the research was to study on the effect of different concentrations of the extract of pandanus leaves (Pandanus amarylifollius) mixed in the seaweed (Eucheuma cottonii) drinking juice on the consumer acceptance. The method used was experimental and composed as non factorial Completely Randomized Design (RAL), which consisted of 4 levels,namely: no pandanus leaf extract (D1), the addition of 20 ml pandanus leaf extract (D2), the addition of 40 ml pandanus leaf extract (D3) and the addition of 60 ml pandanus leaf extract (D4). The parameters used were sensory evaluation, the value of pH, reduction sugar content, the viscosity, and the TPC. The highest consumer acceptance was indicated by the addition of 60 ml pandanus leaf extract (D4) into the the seaweed drinking juice. The percentage of consumer acceptance on the colour was 93.65% (75 consumer), the flavour was 73.75% (59 consumer) and the odour was 91.25% (73 consumer). The value of pH was 6.93, the content of reduction sugar was 28.85%, the value of viscosity was 3.03 cP, and the total plate count bacteria was 83x103 cfu/g.Keywords: consumer acceptance, drinking juice, Eucheuma cottonii, Pandanus amarylifollius, seaweed.